The Effect of Breathing Patterns Common to Competitive Swimming on Gas Exchange and Muscle Deoxygenation During Heavy-Intensity Fartlek Exercise - Grossman, Kevin J.; Lim, David J.; Murias, Juan M.; Belfry, Glen R. (Frontiers in Physiology, 2021)
During competitive freestyle swimming, the change of direction requires a turn followed by ~15m of underwater kicking at various intensities that require a ~5s breath-hold (BH). Upon surfacing, breathing must be regulated, as head rotation is necessary to facilitate the breath while completing the length of the pool (~25s). This study compared the respiratory and muscle deoxygenation responses of regulated breathing versus free-breathing, during these 25s-5s cycles. It was hypothesized that with the addition of a BH and sprint during heavy-intensity (HVY) exercise, oxygen uptake (VO2) and oxygen saturation (SatO2) would decrease, and muscle deoxygenation ([HHb]) and total hemoglobin ([Hbtot]) would increase. Ten healthy male participants (24±3 years) performed 4-6min trials of HVY cycling in the following conditions: 1) continuous free-breathing (CONLD), 2) continuous with 5s BH every 25s (CONLD-BH), 3) Fartlek, a 5s sprint followed by 25s of HVY (FLK), and 4) combined Fartlek and BH (FLK-BH). Continuous collection of VO2 and SatO2¬, [Hbtot], and [HHb] via breath-by-breath gas analysis and near-infrared spectroscopy (normalized to baseline), respectively. Breathing frequency and tidal volumes were matched between CONLD-CONLD-BH and FLK-FLK-BH. VO2 was unchanged between CONLD (2.12±0.35L/min) and CONLD-BH (2.15±0.42L/min; p=0.116), and FLK (2.24±0.40L/min) and FLK-BH (2.20±0.45L/min; p=0.861). SatO2: CONLD (63±1.9%) > CONLD-BH (59±3.3%; p<0.001), but unchanged between FLK (61±2.2%) and FLK-BH (62±3.1%; p=0.462). Δ[Hbtot]: CONLD (3.3±1.6µM) > CONLD-BH (-2.5±1.2µM; ∆177%; p<0.001), but unchanged between FLK (2.0±1.6µM) and FLK-BH (0.82±1.4µM; p=0.979). Δ[HHb]: CONLD (7.3±1.8µM) > CONLD-BH (7.0±2.0µM; ∆4%; p=0.011), and FLK (6.7±1.8µM) < FLK-BH (8.7±2.4µM; p<0.001). It is suggested that the unchanged VO2 between CONLD and CONLD-BH was supported by increased deoxygenation as reflected by decreased ∆[Hbtot] and blunted ∆[HHb], via apneic-driven redistribution of blood flow away from working muscles, which is reflected by the decreased SatO2. However, the preserved VO2 during FLK-BH versus FLK has been underpinned by the increase [HHb].